Psychometric properties of the japanese version of the single dental anxiety question: A cross-sectional online survey - Ogawa Mika; Sago Teppei; Lahti Satu; Taniguchi Shogo (Bentham Science Publishers, 2022)
Background:
Assessment of dental anxiety using a validated questionnaire is important for its management and survey.
Objective:
The aim of this cross-sectional online survey was to evaluate the psychometric properties of the Japanese version of the Single Dental Anxiety Question (SDAQ).
Methods:
The single question was translated into Japanese following the forward-backward method. Four hundred Japanese internet monitors (age 20–79 years) were included in the study. Sensitivity–specificity analysis and the Kappa coefficient were calculated against the Modified Dental Anxiety Scale (MDAS) using the 19 cutoff score for high dental anxiety. Criterion validity was evaluated using age, gender, dental attendance pattern, negative dental experiences, and subjective oral health.
Results:
Among these subjects, 11% were found to have high dental anxiety on the MDAS score and 9% rated themselves as very afraid of SDAQ. The Kappa coefficient between the MDAS cutoff score and the SDAQ classification was 0.58, the sensitivity was 0.56, and the specificity was 0.97. The SDAQ was associated with gender (P = 0.018), dental attendance pattern (P = 0.020), negative dental experiences (P < 0.001), and subjective oral health (P < 0.001).
Conclusion:
The Japanese version of the SDAQ has good criterion and construct validity but lower sensitivity than the original version. It can be used to assess dental anxiety in large dental surveys or clinical settings where a multi-item questionnaire is not feasible.